Migration, Space and Transnational Identities - Conway, D. author. aut Link
IX, 219 p.
Keywords: Twenty years after the post-apartheid Government took office, this timely text interrogates the extent to which the attitudes, identities and everyday lives of British people have changed in accordance with the 'new' South Africa. New ethnographic research is drawn upon to explore important questions of mobility, locality and identity.